Confiscated Asset Management According to The Islamic Perspective - Salleh, Ahmad Dahlan (Alhurriyah, 2024)
This study explores the practice of calculating weton, which has become deeply rooted in the culture of the Javanese community in the Wajak District of Malang Regency, namely, calculating weton to determine wedding dates. The research, employing qualitative methods, aims to investigate or construct claims or explanations behind the facts. Data collection techniques involve observation, interviews, and documentary studies, while data analysis employs deductive methods. The findings reveal that weton consists of a series of seven days in a week: Sunday, Monday, Tuesday, Wednesday, Thursday, Friday, Saturday, and five hari pasaran (market days) for Java, namely Legi, Pahing, Pon, Wage, and Kliwon. When calculating weton, Javanese people generally use three calendars that have existed for a long time: the Saka calendar, the Sultan Agung calendar, and the Pranata Mangsa. Weton is classified as al-‘urf al-fasid (a bad habit or tradition) when seen as a talisman and a way to avoid misfortune. In Islam, belief in misfortune is called tathayyur.